Targeting regulated cell death (RCD) with naturally derived sesquiterpene lactones in cancer therapy - Cong Xu; Shaodi Wen; Xiaoyue Du; Xinhua Zou; Elaine Lai-Han Leung; Guoren Zhou; Qibiao Wu; Bo Shen (Pharmacological Research)
Regulated cell death (RCD) is a type of cell death modulated by specific signal transduction pathways. Currently, known RCD types include apoptosis, autophagy, ferroptosis, necroptosis, cuproptosis, pyroptosis, and NETosis. Mutations in cancer cells may prevent the RCD pathway; therefore, targeting RCD in tumors has become a promising therapeutic approach. Sesquiterpene lactones represent a diverse and extensive class of plant-derived phytochemicals that serve as potential sources for developing various drugs. Recent studies have shown that sesquiterpene lactones have promising potential in cancer treatment. This review systematically summarizes recent progress in the study of sesquiterpene lactones as antitumor agents, highlighting their role in targeting various RCD pathways, including those involved in apoptosis, autophagy, ferroptosis, necroptosis, and cuproptosis. The primary purpose of the present review is to provide a clear picture of the regulation of RCD by sesquiterpene lactones against different targets in various cancers, which will facilitate the development of new strategies for cancer therapy.